Pendidikan, Pelatihan pada Pasangan Suami Siap Siaga sebagai Upaya dalam Pencegahan Kematian Ibu - Thalib, Kiki Uniatri; Raehan, Raehan; Djunaedi, Djunaedi; M, Warda; Sabriana, Riska; Harlina, Harlina (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Preparation for maternal health must begin when a woman is planning a pregnancy, during pregnancy, childbirth, the postpartum and breastfeeding period, the period of using family planning contraception until old age, while the baby's health must be considered from the time the fetus is in the womb, during the birth process, when it is just born. , babies, toddlers, pre-school children, school years to teenagers. The aim of this community service activity is to increase participants' knowledge and motivation in efforts to accelerate the reduction of maternal mortality rates requiring cross-sector support, especially in empowering husbands, wives, families and the community in planning childbirth and being prepared to face obstetric and neonatal complications. Method of community service activities through education and training for husbands who are ready to standby. in the working area of ​​the Manisa Community Health Center, Manisa Village. The results of community service activities through education and training for husband and wife couples who have been implemented have had a positive impact on the knowledge of mothers of reproductive age in the working area of ​​the Manisa Community Health Center, Manisa Village.